Optically Pumped Broadband Terahertz Modulator Based on Nanostructured PtSe2 Thin Films. Issue 7 (22nd January 2020) - Jakhar, Alka; Kumar, Prabhat; Moudgil, Akshay; Dhyani, Veerendra; Das, Samaresh
Abstract: Here, an optically pumped terahertz (THz) modulator based on the novel transition metal dichalcogenide (TMD) material platinum diselenide (PtSe2 ) is demonstrated. The nanostructured PtSe2 thin films are formed by direct selenization of the sputtered platinum film on a high‐resistivity silicon substrate. Raman spectroscopy, scanning electron microscopy, and high‐resolution transmission electron microscopy confirm the formation of polycrystalline PtSe2 nanostructures. The transmission measurements reveal the modulation of the THz waves in the wide frequency range of 0.1–1 THz. The modulation depth of 32.7% is achieved under low pumping laser power of 1 W cm −2 . The numerical analysis based on the finite difference time domain method is in good agreement with the experimentally obtained results. Further, the simulation results manifest that higher modulation depth can be achieved with the utilization of higher laser power. This work provides a path for the application of TMD materials like PtSe2 in the development of THz tunable devices such as modulators, polarizers, filters. Abstract : Nanostructured platinum diselenide thin films on high‐resistivity silicon substrate are employed for optically controlled terahertz (THz) modulation. THz transmission measurements in the wide frequency range of 0.1–1 THz exhibit the modulators to reach up to 32.7% modulation depth even under low pumping power of 1 W cm −2 .